Determination of raw meat freshness by the express method of n ear-IR spectroscopy - Volkov, A.; Litvynchuk (Vorontsova), Svitlana; Kovaleva, Svetlana (My University, 2017)
When raw meat is stored for a long time, many biochemical processes take place inside. As result, new substances, that not typical for fresh meat, are formed. Present of these compounds may be identified by near-IR spectroscopy. If the spectrograph is pre-calibrated, the express method of nondestructive near-IR spectroscopy can be used for objective estimate o f degree o f meat freshness. The use of this method allows to avoid errors in estimation that typical for organoleptic methods.
Keywords: кафедра харчової хімії; кафедра фізики та професійної безпеки; non-destructive IR spectroscopy; raw meat; freshness; неруйнівна ІЧ спектроскопія; сире м’ясо; свіжість; неразрушающая ИК спектроскопия; сырое мясо; свежесть